Problem Based Learning Models to Numeracy Literacy Skills : A Study in Elementary School - Rahmah, Indana Failur; Irianto, Apri; Rachmadtullah, Reza (Journal of Education and Teacher Training Innovation, 2023)
: low numeracy literacy ability of students is a particular concern considering that in this 21st-century learning, students should have mastered this ability. The problem-based learning models is a learning model that presents a contextual problems so that students can be directly involved in the problem-solving process. Thus, this study aims to determine the effect of the problem-based learning model on the numeracy literacy skills of elementary school students. The research method used by researchers is a pre-experiment with one group pretest and posttest design using a quantitative approach. The sample in this study was eleven students in fifth grade at Waru Timur 2 Pamekasan Madura state elementary school. Data collection was carried out by administering tests (pretest and posttest) regarding students’ numeracy literacy abilities. Data were analyzed using descriptive statistics, prerequisite tests, and hypothesis testing with paired samples test. Based on the results of data processing, it is known that there is a significant influence of the use of problem-based learning models on students’ numeracy literacy skills. That is because learning is student-centered so that students can be directly involved in problem-solving